Nutritional composition and lipid oxidation stability of beef patties packed with biodegradable and non-biodegradable materials - Lim, S.L; Wan Rosli, W.I. (Universiti Kebangsaan Malaysia, 2014)
Long term environmental problems of non-biodegradable plastic, the need to conserve finite fossil fuels and the impact of globalization of food supply are some of the driving forces in looking towards biodegradable plastics as an alternative to the existing petrochemical-based polymers for food packaging application. The stability of nutritional composition, lipid oxidation, physical traits of beef patties packed with different types of plastics and the surface morphology of plastics after 3 months of frozen storage (-18 were studied. Beef patties were packed with either non-biodegradable high density polyethylene (PE), hydro-biodegradable low density polyethylene/thermoplastic sago starch plastic (PES), hydro-biodegradable polylactic acid plastic (PLA) or oxo-biodegradable plastic (OXO)). There were no differences in most of the nutrients analyzed and lipid oxidation values of beef patties packed with either biodegradable or non-biodegradable plastics after storage. There were significant (p decreased in fat for cooked patties and moisture for both raw and cooked patties. Lipid oxidation indices of beef patties increased after storage but they were not significant (p Beef patties packed with biodegradable packaging materials were able to retain moisture without jeopardizing the diameter reduction during storage. In summary, the application of biodegradable plastics for packing beef patties was considered acceptable and can be suggested as an alternative packaging item to replace conventional polyethylene plastic packaging.